Upaya Meningkatkan Hasil Belajar Roll Depan Melalui Penggunaan Media Modifikasi Bidang Miring Pada Siswa Kelas IV SD Negeri Ngadirejo 1 Kota Kediri - Rido Sejati; Bambang Yuwono; Weda3 (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The objective of this research is to improve student learning outcomes in Physical Education, Sports, and Health for fourth-grade students at SD Negeri Ngadirejo 1, Kota Kediri, by utilizing an inclined plane. This study is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of two meetings. Each cycle includes planning, implementing actions, observation, and reflection. The research subjects were 22 fourth-grade students at SD Negeri Ngadirejo 1, consisting of 12 male and 10 female students. Data sources were obtained from teachers and students. Data collection techniques included observation and documentation. The results of the study indicate that using an inclined plane as a teaching aid can enhance student learning outcomes from cycle I to cycle II. Before the intervention, the learning process was conventional, resulting in low student motivation and engagement. In cycle I, session 2, there was an improvement in student motivation, engagement, and learning outcomes, although not yet optimal. The implementation of cycle II led to a further increase in student motivation and engagement, as reflected in the average class score, which rose by 9.47 points from 68.56 (categorized as sufficient) in cycle I to 78.03 (categorized as good) in cycle II. Meanwhile, student learning achievement or mastery increased by 45.46%, from 36.36% in cycle I to 81.82% in cycle II. Additionally, student performance in practice, attitude, and knowledge improved from the